Performance of pineapple leaf/glass fibre-reinforced vinyl ester composites utilizing automated spray up technique - Zin, Mohd Hanafee (2019)
This research is aimed at developing optimized process parameters to fabricate pineapple leaf fibre (PALF)-vinyl-ester-based hybrid biocomposites utilising the industrial robotic arm integrated with fibre spray up mechanism. The optimized process parameters are developed through a series of testing using different variable process parameters controlled by the integrated spray gun-robotic arm system. In the preliminary study, material characterization of pineapple leaf fibre (PALF) of 273 tex, was conducted, which include physical, morphological, mechanical, and thermal testing and analysis. PALF yarn fibre with different robot linear travel speed (0.15, 0.23, 0.30, 0.38, and 0.45) m/s reinforced vinyl ester composites are fabricated and characterized based on mechanical (tensile and flexural), thermal (TGA and DMA) and surface morphology. For each mechanical result, coefficient of variance (COV) is calculated to measure the variability of the mean distribution. The optimum robot linear travel speed obtained is 0.23 m/s, which produced composite with density of 1.12 g/cm3 and fibre volume fraction of 27.4%. The COV for 0.23 m/s robot speed sample is 9.51%, with the highest tensile strength of 28.70 MPa. The analysis of spray angle showed optimum spray angle of 70°, whereby spray distribution of the chopped fibre showed highest degree of uniformity (COV 5.84%), as well as high mechanical strength. Linear spray pattern produced more uniform fibre and resin distribution as compared to circular and cross, whereby a lot of overlap fibre distribution occurred, which affect thickness consistency throughout the sample. Thermal analysis showed that linear pattern resulted in the highest Onset Oxidation Temperature (OOT) at 397.56°C, while circular pattern recorded the maximum char residue at 5.78%. The length of pineapple yarn consists of 3 different combination, namely as L1 (130 - 150) mm, L2 (530 - 550) mm and L3 (130 – 550) mm. The mechanical analysis depicted that L1 resulted in the highest tensile strength (29.20 MPa), while L3 resulted in better mechanical properties consistency. All optimized parameters are later used to fabricate the glass-PALF-VE hybrid biocomposites. The mechanical analysis showed that the hybrid biocomposites recorded 171.61% higher in tensile strength as compared to PALF-VE composite alone. The investigation of optimized process parameters will pave the way towards greater usage of PALF as input for robotic spray up process and potentially to be scaled up in industrial mass production.